Towards an intercultural religious education: recovering memory - Montoya Hernández, María Auxiliadora (2019)
Religious education through an intercultural approach is urgent for Costa Rican society, a multiethnic and multicultural nation. The convergence between ethnic, cultural, and religious diversity is something that needs to be addressed at once. Being able to recover the historic memory of religious education in Costa Rica is imperative to understand the roads and positions it has taken, as well as the struggles experienced through different points in time. All this with the purpose of taking a new way towards an approach of interculturality to encourage respect for diversity and coexistence in schools. Educating through an intercultural focus is supposed to guide people to coexist in a society where cultural, ethnic, and religious diversity is not only legit and regulated by Costa Rican constitutional rules, but also seen as a value and an asset. A religious education guided by this focus will encourage student interaction, mutual support, human rights of those in the education system, solidarity, and respect towards all people. In addition, it will value and appreciate differences, contributions from other cultures, religious expressions and spiritual wisdom in the aim to construct more equal and inclusive societies. Interculturality will then be an essential dimension towards mutual growth and humanization. Keywords: Interculturality, religious education, diversity, national identity, equality